Aberrant gene methylation and bronchial dysplasia in high risk lung cancer patients. (April 2016) - Rosell, A.; Rodríguez, N.; Monsó, E.; Taron, M.; Millares, L.; Ramírez, J.L.; López-Lisbona, R.; Cubero, N.; Andreo, F.; Sanz, J.; Llatjós, M.; Llatjós, R.; et al.
Highlights: In a high risk patients for lung cancer, high grade dysplasia is found in 15.6%. In the same group, aberrant methylation in bronchial secretions is found in 61.2%. Bronchial washing additionally detects 41.7% of methylation to induced sputum analysis. DAPK1 is the most frequent methylated gene (52%), 20.4% for p16 and 3.1% for RASSF1A. High grade dysplasia and methylation in bronchial secretion concur in 11.2%. Abstract: Introduction: The risk for lung cancer is incremented in high degree dysplasia (HGD) and in subjects with hypermethylation of multiple genes. We sought to establish the association between them, as well as to analyze the DNA aberrant methylation in sputum and in bronchial washings (BW). Methods: Cross sectional study of high risk patients for lung cancer in whom induced sputum and autofluorescence bronchoscopy were performed. The molecular analysis was determined on DAPK1, RASSF1A and p16 genes using Methylation-specific PCR. Results: A total of 128 patients were enrolled in the study. Dysplasia lesions were found in 79 patients (61.7%) and high grade dysplasia in 20 (15.6%). Ninety eight patients out of 128 underwent molecular analysis. Methylation was observed in bronchial secretions (sputum or BW) in 60 patients (61.2%), 51 of them (52%) for DAPK1, in 20 (20.4%) for p16 and in three (3.1%) for RASSF1A. Methylated genes only found in sputum accounted for 38.3% and only in BW in 41.7%, and in both 20.0%. In the 11.2% of the patients studied, HGD and a hypermethylated gene were present, while for the 55.1% of the sample only one of both was detected and for the rest of the subjects (33.6%), none of the risk factors were observed. Conclusions: Our data determines DNA aberrant methylation panel in bronchial secretions is present in a 61.2% and HGD is found in 15.6%. Although both parameters have previously been identified as risk factors for lung cancer, the current study does not find a significative association between them. The study also highlights the importance of BW as a complementary sample to induced sputum when analyzing gene aberrant methylation.